Does water fluoridation influence ethnic inequalities in caries in Brazilian children and adolescents?. Issue 4 (2nd August 2021) - Bomfim, Rafael Aiello; Watt, Richard G.; Tsakos, Georgios; Heilmann, Anja; Frazão, Paulo
Abstract: Objectives: This study aimed to investigate the influence of community water fluoridation on ethnic inequalities in untreated dental caries among children and adolescents in Brazil while taking the human development context into account. Methods: Data from a nationwide Brazilian epidemiological population oral health survey were used (SB Brazil 2010). Outcomes were caries prevalence measured by the proportion of individuals with one or more untreated decayed teeth and caries severity defined by the mean number of untreated decayed teeth (DT). Three different contexts were considered: 1—cities with no water fluoridation; 2—cities with water fluoridation and low Human Development Index (HDI); and 3—cities with water fluoridation and high HDI. The exposure was ethnic/racial group (White, Pardo, Black) and covariates were age, sex and household income. Multilevel logistic and negative binomial regressions were performed with 6696 children (aged 5 years) and 11 585 adolescents (aged 12 and 15‐19 years). Results: For both children and adolescents, ethnic differences in caries prevalence and mean DT were found in the nonfluoridated cities with low HDI and also in cities with high HDI, most of which were fluoridated. For example in nonfluoridated cities with low HDI, 5‐year‐old Pardo children were more likely to have untreated decay (OR = 1.22; 95% CI: 1.02, 1.46) and had more decayed teeth (RR = 1.18; 95% CI: 1.04, 1.34) than their White counterparts after adjusting for sex and household income. No statistically significant differences were observed in fluoridated cities with low HDI. Conclusion: Water fluoridation appears to be associated with reduced ethnic inequalities in dental caries prevalence and mean DT among children and adolescents in more disadvantaged settings.